MARKETING MIX STRATEGY TO ATTRACT CUSTOMERS: CASE STUDY OF SALSA VERDE RESTAURANT IN GRAND HYATT BALI - Hurdawaty, Ramon; Pratama, Alvin (International Conference on Cultural Studies; Vol 2 (2019): Proceedings International Conference on Cultural Studies, 2019)
Salsa Verde Restaurant is part of the Grand Hyatt Nusa Dua Hotel, Bali, located in ITDC which is an elite complex on the beach and has an Italian restaurant concept. To attract the interest of guests, many innovative and good quality services are needed and supported by the right strategy and agreed upon by the restaurant management. This study aims to obtain information about the marketing mix strategies used and the best strategies to use in the salsa verde restaurant. In this study there is one variable that is processed using descriptive qualitative methods using SWOT Analysis, EFAS matrix, IFAS, IE and QSPM. The results of the study it was found that the strategy that must be done by Salsa Verde Restaurant is to repair or replace the work support tools in the kitchen and service, improve service quality and prices for guests, improve product quality to be the best, optimize and improve the work system that has been implemented, improve old menus both from material or from display presentation, and optimize promotion through existing media.